PENGARUH CITY BRANDING PADA CITY IMAGE DAN KEPUTUSAN BERKUNJUNG WISATAWAN KE KABUPATEN PURWAKARTA - Jesi Indriani; Chandra Kuswoyo (Universitas Kristen Maranatha, 2017)
This research aims to investigate the influence of city branding on city image, investigate the influence of city branding on decision to visit, and investigate the influence of city image on decision to visit. The research method used in this study is explanatory research. Sample of 156 tourist visiting the tourist attractions in Purwakarta. Method of data is collection questionnaire, causal explanatory, and using Path Analysis. The result showed that city branding variable (X) significantly influence on city image (Y1) about 40,7%, city branding variable (X) significantly influence on decision to visit (Y2) about 11,5%, city image variable (Y1) significantly influence on decision to visit (Y2) about 19,5%, and also city branding variables (X) and city image variable (Y1) significantly influence on decision to visit (Y2) about 50,20%. The conclusion of this research is a significant effect on city branding impact city image and decision to visit Purwakarta city.Keywords: city branding, city image, and decision to visit.